Decentralised systemising of Scholarship of Engagement in higher education towards societal impact - September-Brown, P.; Daniels, P.; Hart, C. (South African Journal of Higher Education, 2023)
In this article, a case study is presented for the development of a Scholarship of Engagement (SoE) engagement database, to map the engagement footprint of the university, and develop a Knowledge Management System (KMS) at the University of the Western Cape (UWC), in order to facilitate the process of knowledge sharing. The aim of this article is to discuss a process of creating baseline data, to explore and profile the institution’s SoE landscape, and facilitate a decentralised system of the SoE, based on an integrated approach to the institutionalisation of the SoE. The sharing of exemplars are important; consequently, in this article the context and role of the Community Engagement Unit (CEU), as well as the motivation for embarking on the project are explained. Additionally, the process from conceptualization, through implementation, to reflections on lessons learnt, and the future path of decentralisation, are plotted and documented. All partners pilot an integrative approach to implementation, to facilitate acceptance and uptake, while enablers that facilitate the process are identified, and decentralisation for the protection of academic freedom is highlighted. This case study is relevant to other universities, especially those on the African continent, as we attend to the broader decolonialisation agenda, which presents an exemplar for the duplication, adaptation, and creation of a SoE database, for universities to profile and present their anchoring in communities, following the principles of engagement that are aligned to transformation and social justice.